Highly Conductive Stretchable All‐Plastic Electrodes Using a Novel Dipping‐Embedded Transfer Method for High‐Performance Wearable Sensors and Semitransparent Organic Solar Cells - Fan, Xi; Xu, Bingang; Wang, Naixiang; Wang, Jinzhao; Liu, Shenghua; Wang, Hao; Yan, Feng (Advanced electronic materials, 2017)
Conducting polymer (CP) is a key component of wearable, flexible, and semitransparent electronics. As a classic CP, highly conductive PEDOT:PSS has been achieved on glass via strong acid treatments. However, it is a great challenge to realize highly conductive stretchable films of PEDOT:PSS, due to limits of strong acid treatments and poor intrinsic stretchability of as‐cast films. Herein, a highly conductive stretchable all‐plastic electrode of CP embedded into PDMS elastomers (PEDOT:PSS–PDMS) via a dipping‐embedded transfer method is reported. The method enables large‐area PEDOT:PSS films that are transferred from quartz to PDMS. The PEDOT:PSS–PDMS films have high conductivity of 2890 S cm−1 and an enhanced stretchability of 20% strain. Underlying mechanisms of high yield of the large‐area productions, high conductivity, and improved stretchability are investigated. Furthermore, two types of devices including wearable strain sensors and semitransparent organic solar cells (OSCs) are fabricated using the films. The wearable sensors show high gauge factor of ≈22 under 20% strain and the OSCs exhibit a power conversion efficiency of 3.75% and 3.46% when lights are illuminated from PDMS and indium tin oxide, respectively. Highly conductive stretchable all‐plastic electrodes are prepared via a novel dipping‐embedded transfer method with substantial advantages, including high yield large‐area production, little acid residue, and enhanced stretchability. The films induce 4‐fold sensitivity enhancement for wearable strain sensors and over 30% increase in power conversion efficiency for semitransparent organic solar cells.